Anxiety and Self-esteem as Causes and Consequences of Cyber-victimization in Preadolescence: A Longitudinal Study - David Álvarez-García; Trinidad García; Lucy Betts (European Journal of Psychology Applied to Legal Context)

(untitled)
Background/Objective: In recent years, the use of electronic communication devices at early ages has become widespread, promoting concern about the possible risks associated with technology use. This research explores the connection between being a victim of online aggression, and anxiety and low self-esteem by analysing: 1) the level and developmental trajectory of anxiety and self-esteem; 2) the effect of anxiety and self-esteem in 4th and 5th grade of Primary Education on cyber-victimization in 6th grade, both directly and mediated by risk internet behaviours; and 3) the effect of cyber-victimization in 6th grade on anxiety and self-esteem in that same year. Method: A three-year longitudinal study was undertaken with 268 students attending nine schools in Asturias (Spain). Participants completed measures at three timepoints, separated by a year interval: when they were in 4th, 5th, and 6th grade. In 4th and 5th grade, self-report scales of anxiety and self-esteem were administered. In 6th grade, self-report scales of risk internet behaviors and cyber-victimization were also administered. Results: An increase in anxiety and a decrease in self-esteem from 5th to 6th grade was found. There was also an indirect effect of anxiety and self-esteem in 5th grade on cyber-victimization in 6th grade, mediated by risk internet behaviors. Cyber-victimization in 6th grade negatively impacted anxiety and self-esteem in that same year. Conclusions: The results obtained in this work suggest a bidirectional relationship between anxiety/low self-esteem and cyber-victimization.